2006
DOI: 10.1063/1.2220552
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the red luminescence in Mg-doped GaN

Abstract: Optically-detected magnetic resonance (ODMR) and positron annihilation spectroscopy (PAS) experiments have been employed to study magnesium-doped GaN layers grown by metal-organic vapor phase epitaxy. As the Mg doping level is changed, the combined experiments reveal a strong correlation between the vacancy concentrations and the intensity of the red photoluminescence band at 1.8 eV. The analysis provides strong evidence that the emission is due to recombination in which electrons both from effective mass dono… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Positron annihilation is a non-destructive characterization tool, and there is no limitation on the sample conductivities or the measurement temperatures. Vacancy-type defects in group-III nitride semiconductors have been investigated using this method [2][3][4][5][6][7][8][9][10][11][12], and the results show that positrons are a powerful probe for studying cation vacancies, vacancy clusters, and vacancy-impurity complexes.…”
Section: Introductionmentioning
confidence: 98%
“…Positron annihilation is a non-destructive characterization tool, and there is no limitation on the sample conductivities or the measurement temperatures. Vacancy-type defects in group-III nitride semiconductors have been investigated using this method [2][3][4][5][6][7][8][9][10][11][12], and the results show that positrons are a powerful probe for studying cation vacancies, vacancy clusters, and vacancy-impurity complexes.…”
Section: Introductionmentioning
confidence: 98%
“…noted and sometimes dominates the PL spectra. [10][11][12][13][14] We show such spectra in Fig. 5 for MOCVD grown samples, measured under different excitation conditions.…”
Section: B the Dap Spectrum At 327 Evmentioning
confidence: 99%
“…10 In the deep red spectral region there is a broad band observed at about 1.8 eV, suggested as related to a deep Mg-related complex defect. [12][13][14] In this paper, we will present additional PL and CL data obtained from MOCVD-grown GaN:Mg samples on low defect density bulk GaN substrates. These data allow a more definite identification of the above-mentioned characteristic ABE and DAP spectra for GaN:Mg.…”
mentioning
confidence: 99%
“…The ODMR spectra change drastically when the samples are annealed but here, we report only on spectra seen in unannealed material when monitoring emission in the green-yellow region ͑the same samples have previously been the subject of a positron annihilation investigation combined with an ODMR study of PL in the red region͒. 7 An ODMR study of these samples following annealing has also been reported previously 8 and has led to a detailed model for the Mg acceptor states. A description of the detailed behavior of the ODMR and PL signals under a range of annealing processes will be reported separately.…”
Section: A Details Of the Specimensmentioning
confidence: 81%
“…31 The present experiments provide the first evidence that interstitial gallium can be present in as-grown magnesium doped GaN, the data suggesting that it is associated with ͑and thus compensating͒ the magnesium acceptors. In a separate study of these specimens in which we have combined ODMR with positron annihilation spectroscopy, 7 we have found evidence that in as-grown Mg-doped GaN there exist a large number of vacancies. Annealing is found to reduce this number; at the same time, the spectra observed in the present study disappear.…”
Section: Discussionmentioning
confidence: 93%